Benchmarking Taxonomic and Genetic Diversity After the Fact: Lessons Learned From the Catastrophic 2019–2020 Australian Bushfires - Catullo, Renee A.; Schembri, Rhiannon; Tedeschi, Leonardo Gonçalves; Eldridge, Mark D. B.; Joseph, Leo; Moritz, Craig C. (Frontiers in Ecology and Evolution, 2021)
Environmental catastrophes are increasing in frequency and severity under climate change, and they substantially impact biodiversity. Recovery actions after catastrophes depend on prior benchmarking of biodiversity and that requires critical assessment of taxonomy. Long-term recovery of species also requires an understanding of within-species diversity. Australia’s 2019-2020 bushfires were unprecedented in their extent and severity and impacted large portions of habitats that are not adapted to fire. Assessments ofthe fires’ impacts on vertebrates identified 114 species that were a high priority for management. In response, we compiled explicit information on taxonomic diversity and genetic diversity within fire-impacted vertebrates to provide to government agencies undertaking rapid conservation assessments. We identified a significant number of candidate species, particularly in frogs and mammals. Reptiles and mammals also had high levels of intraspecific genetic structure relevant to conservation management. The first challenge was making published genetic data fit for purpose because original publications often focused on a different question and did not provide raw sequence read data. For many species, significant unpublished data was held by researchers. Summarising sampling gaps across species revealed that many areas were poorly sampled across taxonomic groups. To prepare responses to future catastrophes, we recommend that researchers embrace open data principles including providing detailed metadata. Governments need to invest in a skilled taxonomic workforce to document biodiversity before an event and to assess its impacts afterwards. Natural history collections should also target increasing their DNA collections and revise their collection strategies to increasingly take population-scale DNA samples.